Small Businesses as a Factor for Growth and Regional Economic Development in Brazil - Ana Claudia Arruda Laprovitera; Dinilson Pedroza Junior (European Regional Science Association (ERSA), 2010)
The objective of the article is to analyze the role of small (businesses) companies in regional economic development. The article analyzes the current structure of tax concession and financial incentives into improving regional development and how it can be modified and directed in promoting small companies, especially the small enterprises located in poor regions of Brazil. We discuss how the incentives for regional development can be used to foment small business environment in poor regions, more specifically, in the Northeast of Brazil. A small business environment is a set of social, economic and institutional spaces where such companies operate, considering its opportunities and threats. The small companies are understood - in the vision of the official institutions of Brazil - as units of production of goods and services of reduced scale. This concept considers the formal organizations (with legal register and tax contributions), excluding the informal sectors of the economy. The size of a company, its number of employees and its market share are criterias usually applied to the definition of small companies. We argue that tax and finances incentives to the small company in north-eastern of Brazil must consider the scenarios techniques, as anticipations of futures, conditioned of the determined hypotheses. The methodology of construction of scenarios constitutes a tool for anticipation of the events, delimiting its probabilities and organizing the uncertainty. It is assumed that the scenarios of small business environment are influenced by the national economic, political and institutional contexts. The work is based in social, economic and institutional sceneries available for Brazil adapted for the environment of the small companies of Brazilian northeast.
Keywords: 330